Redox-active, luminescent coordination nanosheet capsules containing magnetite - Arai, Ryo (Sci Rep, 2020)
Two-dimensional coordination nanosheets (CONASHs) are grown at the spherical liquid–liquid interface of a dichloromethane droplet in water to form zero-dimensional nano- and micro-capsules using a simple dropping method, a syringe-pump method, and an emulsion method. Reaction of 1,3,5-tris[4-(4′-2,2′:6′,2″-terpyridyl)phenyl]benzene (1) with Fe(BF(4))(2) affords electrochromic Fe(tpy)(2) CONASH capsules and that of ligand 1 with ZnSO(4) does photoluminescent Zn(2)(μ-O(2)SO(2))(2)(tpy)(2) CONASH capsules. Fe(tpy)(2) CONASH capsules containing magnetite particles were produced by the syringe-pump method by adding magnetite to the aqueous phase, with the assembly and dispersion of the magnetite-containing CONASH capsules being easily controlled with a magnet. This indicates that physicochemically functional CONASH capsules are suitable for incorporating other functional materials to develop hybrid systems.